Rasa Percaya Diri, Motivasi, Dan Kecemasan Dalam Olahraga Bulutangkis - Yapsir G. Wirawan (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 1999)
This study was intended to obtain data on the psychological status of badminton players which are needed in order to help raise achievement.The research subjects were 41 badminton players, male and female, taken from a badminton club in Semarang.The measurement instruments used in this study were tests intended to reveal self-confidence, motivation and anxiety. These instruments had been adapted to Indonesia and their reliability and validity had been reestablished. Data on badminton achievement, in terms of player’s levels, were taken from documents recorded by coaches.Pearson Product Moment correlation technique was employed to find out relationships between research variables, while t-test was employed to find differences between males and females in those variables. Results indicated that : (1) No significant difference was found in self confidence, motivation an anxiety between male and female athletes (2) In general, the badminton athletes had low self confidence, quite high motivation and low anxiety (3) There was a positive and significant relationship between player’s level and motivation. Key words : bulutangkis, percaya diri, motivasi dan kecemasan